Using Time Limits to Improve Patient Visits & Clinic Flow at a Student-Run Free Clinic - Stephens, Dylan; Ramedani, Shayann; Tupinio, Maegan; Lambert, Kristin; Artrip, Rick (Journal of Student-Run Clinics, 2020)
Background: Student-run free clinics often have difficulties with long visits, which are associated with patient dissatisfaction. LionCare, a free clinic run by Pennsylvania State University College of Medicine medical and physician assistant students, experiences similar difficulties. This study sought to gather baseline data on the duration of each step of a patient visit and to evaluate whether implementing a time limit on the longest step would improve clinic flow and affect patient satisfaction. Methods: Data was collected from LionCare’s General and Neurology clinics. Each step of a patient’s visit was recorded, including Time of Arrival and Departure as well as duration of Waiting Room; Vitals; History and Physical (H&P); Presentation to Physician; Seeing Patient with Physician; Medications, Vaccines, Tests, Other. In order to gauge patient satisfaction, short surveys based on select Press Ganey questions were administered at the end of each visit before and during the intervention. Results: Five months of baseline data from 44 visits indicated that H&Ps took the longest of all the steps of a patient visit at 30 minutes. Over 19 visits, a time limit of 25 minutes reduced H&P duration by 10 minutes (p<0.001); duration of Presentation to Physician by 6 minutes (p=0.002); Medications, Vaccines, Tests, Other by 4.5 minutes (p=0.03); and Total Patient Visit by 20 minutes (p=0.002). Patient Satisfaction remained stable before (n=10) and after (n=13). Conclusions: A 25-minute time limit reduced the duration of H&Ps, subsequent steps in the visit, and the overall visit more than expected, thus improving clinic flow. Importantly, patient satisfaction scores remained steady. Thus, at LionCare, placing a time limit on H&Ps was an effective way to improve clinic flow without sacrificing quality.